Candidate Classroom Teachers' Perceptions about being Scientific in the Context of Pseudoscience - Hüseyin Es; Halil Turgut (Seyit Ahmet Kıray, 2018)
The current study, aiming at investigating the perceptions of candidate classroom teachers for being scientific and examining the effect of the intervention comprising particular characteristics of demarcation on those perceptions, was interpretative in nature. Two data sources were utilized in order to determine their pre and post perceptions. Candidates performed poorly in the process of concluding on the status of pseudoscientific knowledge claims. But, after the intervention that based on pre-determined characteristics, the guided participants were seemed to reason more validly and able to evaluate the status of the cases they investigated for being scientific or not.